2018
DOI: 10.5194/tc-2018-117
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Representation of basal melting at the grounding line in ice flow models

Abstract: Abstract. While a lot of attention has been given to the numerical implementation of grounding lines and basal friction in the grounding zone, little has been done about the impact of the numerical treatment of ocean-induced basal melting in this region. Several strategies are currently being employed in the ice sheet modeling community, and the resulting grounding line dynamics may differ strongly, which ultimately add significant uncertainty to the projected contribution of marine ice sheets to sea level ris… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 19 publications
1
27
2
Order By: Relevance
“…Our experimentation revealed that the use of sub-grid melting increases the ability of glacier grounding lines to retreat, leading to faster ice loss. Although the numerical veracity of this approach has been questioned 57 , we have previously found little evidence for a grid-size dependency in using this scheme 19 and find instead that it enables simulated mass loss under warmer-than-present palaeoclimate scenarios that is more closely in agreement with proxy reconstructions that when sub-grid melting is omitted 56 . In support of this approach are recent observations confirming that oceanic water intrudes into the grounding zone of marine-terminating Antarctic glaciers in some areas 58 , carrying with it heat available for melting of ice.…”
Section: Methodsmentioning
confidence: 86%
“…Our experimentation revealed that the use of sub-grid melting increases the ability of glacier grounding lines to retreat, leading to faster ice loss. Although the numerical veracity of this approach has been questioned 57 , we have previously found little evidence for a grid-size dependency in using this scheme 19 and find instead that it enables simulated mass loss under warmer-than-present palaeoclimate scenarios that is more closely in agreement with proxy reconstructions that when sub-grid melting is omitted 56 . In support of this approach are recent observations confirming that oceanic water intrudes into the grounding zone of marine-terminating Antarctic glaciers in some areas 58 , carrying with it heat available for melting of ice.…”
Section: Methodsmentioning
confidence: 86%
“…The grounding line position is determined using hydrostatic equilibrium, with sub-cell treatment of the friction and a modified 30 driving stress (Cornford et al, 2016). The melt rate is applied only for fully-floating cells (as in (Seroussi and Morlighem, 2018)) and is composed of a base rate and the anomalies specified in the individual experiments. The base melt rate is time varying and designed to prevent ice shelf thickening but permit thinning where flux divergence in the shelf is positive.…”
Section: A2 Bisi-lbl: Bisiclesmentioning
confidence: 99%
“…The grounding line position is determined using hydrostatic equilibrium, with sub-element parameterization of the friction (Seroussi et al, 2014). The melt rate is applied only for full-floating elements (Seroussi and Morlighem, 2018) and is initialized using mean rates of ocean estimates over the 2004-2015 period (Schodlok et al, 2016), that are kept constant with time. The surface mass balance is from RACMO2.1 1979-2010 mean (Lenaerts et al, 2012).…”
Section: A7 Issm-jpl: Ice Sheet System Model -Jplmentioning
confidence: 99%
See 1 more Smart Citation
“…This is determined in MALI by evaluating the hydrostatic ice floatation criterion at the center of each grid cell. Note that because of the dual grid implementation used in MALI (Hoffman et al, ), this convention leads to treatment of melting near the grounding line in a fashion similar to, but not identical to, the SEM1 melt parameterization described by Seroussi and Morlighem ().…”
Section: Methodsmentioning
confidence: 99%